2021
DOI: 10.26460/mmud.v5i2.11640
|View full text |Cite
|
Sign up to set email alerts
|

Peran Kecerdasan Spiritual Dan Gaya Hidup Hedonisme Dalam Manajemen Keuangan Pribadi Mahasiswa Di Kota Bandar Lampung

Abstract: Penelitian ini bertujuan untuk menguji dan menganalisis pengaruh variabel independen Kecerdasan Spiritual dan Gaya Hidup Hedonisme terhadap variabel dependen Manajemen Keuanngan Pribadi Mahasiswa di Kota Bandar Lampung. Metode yang digunakan dalam penelitian dengan kuesioner. Sampel dari penelitian ini berjumlah 50 responden. Uji statistic dilakukan dengan Structurel Equation Modelling berbasis PLS, Uji validitas menggunakan nilai factor loading, sedangkan uji realibilitas menggunakan nilai Cronbach’s alpha, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
1
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
2
1
0
4
Order By: Relevance
“…Several factors influence online purchases, including alterations in consumer behavior and way of life (Saputro & Handayani, 2016). This research's findings are consistent with those of Ramadhan (2021), who discovered that a hedonistic lifestyle has no substantial effect on the financial management of college students.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Several factors influence online purchases, including alterations in consumer behavior and way of life (Saputro & Handayani, 2016). This research's findings are consistent with those of Ramadhan (2021), who discovered that a hedonistic lifestyle has no substantial effect on the financial management of college students.…”
Section: Resultssupporting
confidence: 89%
“…They can also instruct wealthy individuals on how to improve their own successful money management skills (Sina and Noya, 2012). This research's findings are congruent with those of Ramadhan (2021), who discovered that spiritual intelligence had a substantial and positive effect on students' financial management skills. This demonstrates how the spiritual intelligence of students can assist them in making prudent financial choices as logical creatures.…”
Section: The Impact Of Spiritual Intelligence On Personal Financial M...supporting
confidence: 85%
“…Those with high spiritual intelligence, they can awaken their ukhrawi soul to create positive actions and deeds. Ferdinan Ramadan has also conducted quantitative scientific research about the influence of spiritual intelligence and hedonistic lifestyle in student personal financial management in the city of Bandar Lampung concluded that aspects of spiritual intelligence have a positive and significant effect on student financial management, the higher the student's spiritual intelligence, the better as well as financial management (Ramadhan et al, 2021), so that the spiritual intelligence that the Prophet warned about. can be the main solution to get out of the life of rampant capitalist hedonism.…”
Section: Hereafter Oriented Struggle and Spiritual Intelligencementioning
confidence: 99%
“…Sedangkan untuk faktor gaya hidup hedonisme, dinyatakan memiliki pengaruh negatif pada manajemen keuangan pribadi, selaras dengan studi Kosyu et al (2014), Nurvitria (2015), dan Ramadhan et al (2021). Hal tersebut diakibatkan karena gaya hidup hedonisme dapat menimbulkan sifat boros yang merupakan salah satu faktor terjadinya impulsive buying.…”
Section: Pendahuluan Latar Belakangunclassified
“…Hal tersebut memiliki arti bahwa dalam melakukan manajemen keuangan pribadi, mahasiswa akan dipengaruhi oleh gaya hidup hedonisme. Maka, mahasiswa yang menganut gaya hidup hedonisme dengan tingkat tinggi akan melakukan manajemen finansialnya dengan buruk (Ramadhan et al, 2021). Kosyu et al (2014) berpendapat bahwa konsumen yang berbelanja dengan gaya hidup hedonisme dan membuat belanja menjadi sebuah gaya hidup akan memicu terjadinya pembelanjaan impulsif.…”
Section: Pengaruh Gaya Hidup Hedonisme Terhadap Manajemen Keuangan Pr...unclassified